Increasing student literacy through story writing activities based on pictures at MINWA special schools - Habibaturrahmah Habibaturrahmah (Pascasarjana Universitas Negeri Makassar, 2022)
This article aims to find out the importance of increasing literacy through writing stories based on pictures, grouping and implementing strategies for writing stories based on pictures, as well as knowing the obstacles and solutions encountered in writing stories based on pictures. The subjects in this article are students with special needs at the MINWA Special School with autism, deafness and mild mental retardation. Based on the ideas in this article, the application of literacy in writing stories based on pictures for children with special needs in Minwa Special Schools is divided into three groups. The first group is for children with special needs who have low intellectual ability, language and creativity, and the second group is for children with special needs who have good intellectual, language and creativity abilities, and the third group is for children with special needs who have intellectual, language and creativity abilities. good. Literacy in writing stories is useful for improving the language skills of students with special needs at MINWA special schools.